2009
DOI: 10.1111/j.1524-4733.2009.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Validation of an Optimally Weighted Patient-Based Utility Index by Application to Randomized Trials in Breast Cancer

Abstract: The scoring algorithm for the UBQ-C utility index can be optimized in different clinical contexts to reflect the relative importance of different aspects of quality of life to the patients in a trial. It can be used to generate sensitive and responsive utility scores, and quality-adjusted life-years that can be used within a trial to compare the net benefit of treatments and inform clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“… 24 26 Only one study, from Australia, reported use of the cancer-specific measure UBQ-C and the subscales were converted to a utility index. 15 …”
Section: Resultsmentioning
confidence: 99%
“… 24 26 Only one study, from Australia, reported use of the cancer-specific measure UBQ-C and the subscales were converted to a utility index. 15 …”
Section: Resultsmentioning
confidence: 99%
“…Ongoing work is needed to support the validity of the utility index. A companion article describes the application of the scoring algorithm to independent trial datasets in breast cancer, and provides further evidence to support its validity by comparison with clinical data [28]. We have also reported on a comparison of the value and sensitivity of utility scores generated by the index to those generated by the EQ‐5D in colorectal cancer [71].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of optimizing the algorithm is to reflect the differences in importance that patients with different types and stages of cancer, and treatments assign to various dimensions of HRQL [40,74]. The implications of optimizing the algorithm for different treatment contexts are addressed by application and discussion in a companion article [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation